Thyroid Stimulating Hormone (TSH) Estimation using Point of Care Testing Devices - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Since the development of the first Point-of-care Testing device (POCT) in 1962, POCTs have found their way into nearly every facet of laboratory diagnostics due to their rapid turn-around-times, testing convenience, ease of use, and relatively lower costs. This review provides an update on the progress in the development of POCTs for TSH assays while highlighting the challenges of these methods and suggesting ways of overcoming them. To achieve this, a literature search of the appropriate databases (Google Scholar, MEDLINE, Science Direct, and PubMed) was conducted using the keywords: POCT, TSH, hyperthyroidism, and hypothyroidism. Relevant articles were identified, duplicates eliminated, then critically analyzed, and discussed in terms of their relevance to the research questions. The different sensitivities of the POCTs reported in the scientific literature are traceable to the peculiarities of the detection technique adopted and the sensitivity of the immune complex recognition, i.e., labelled versus unlabeled immunoassay methods. The main factors limiting the wide acceptance of POCTs are concerns over their clinical usefulness, accuracy, and data (in)security. Routine assessment of the technical competence of POCT operators and regular quality checks of the performance of these devices are critical to maintaining the clinical usefulness of POCTs in TSH measurement. Finally, further research is required to understand the dynamic expectations of clinicians regarding POCT use in diagnosing thyroid dysfunction especially in low- and middle-income countries where data on this subject is lacking.